HYDRATES FORMATION PREDICTION IN PRODUCTION LINES OF X-FIELD BASED ON PRESSURE AND TEMPERATURE PROFILE - MAULIDYASTI FARESTIANA (NIM: 22208043), ESTY
In a gas reservoir, formation of hydrates is a common problem. To avoid the formation of hydrates that will potentially disrupt the production system, one way is predicting the presence of hydrates in the flow, especially at the potential points which hydrates will form. Hydrate formation is preceded by a gas condensation, where the water vaporizes out from the gas because the temperature fell through the dew point, and then the hydrogen bonds formed the water nests. High pressure is needed to shed the guest molecules such as natural gas and impurities within the gas to enter the water nest, and then solidify the form of hydrate crystal structure. This thesis is performed to determine the formation of hydrates on the actual field X using Software OX. For the pipeline system at start-up condition, in terms of temperature, is potentially could form hydrates. More lower the rate, more getting into the area of hydrate formation (Highest DTHYD 18 MMscfd = 57,3oF; Lowest DTHYD 100 MMscfd = 12,55oF).